2000
DOI: 10.1200/jco.2000.18.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Improving Survival Without Reducing Quality of Life in Small-Cell Lung Cancer Patients by Increasing the Dose-Intensity of Chemotherapy With Granulocyte Colony-Stimulating Factor Support: Results of a British Medical Research Council Multicenter Randomized Trial

Abstract: Increasing the dose-intensity of ACE with G-CSF support improved survival while maintaining acceptable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
2
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(93 citation statements)
references
References 19 publications
5
82
2
4
Order By: Relevance
“…The rate or TRT was lower for patients receiving ACE (58%) than those receiving PE (74%). The reason for this is unclear, but is likely to reflect the worse toxicity seen with ACE, and is similar to the 51 -54% reported in comparable studies (Thatcher et al, 2000;Ardizzoni et al, 2002). Higher TRT rates have also been reported for other platinum combinations (Lorigan et al, 2005;Thatcher et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…The rate or TRT was lower for patients receiving ACE (58%) than those receiving PE (74%). The reason for this is unclear, but is likely to reflect the worse toxicity seen with ACE, and is similar to the 51 -54% reported in comparable studies (Thatcher et al, 2000;Ardizzoni et al, 2002). Higher TRT rates have also been reported for other platinum combinations (Lorigan et al, 2005;Thatcher et al, 2005).…”
Section: Discussionsupporting
confidence: 61%
“…S Baka et al lower than that reported for two studies from the UK Medical Research Council, but these studies had fewer ED patients (Thatcher et al, 2000;Thatcher et al, 2005). The median and 2-year survivals for PE in LD patients in our study were lower than those reported by Sundstrom (12.6 vs 14.5 months,21 vs 25%,respectively).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations